Impact of Early Loss of Lower First Permanent Molars on Third Molar Development and Position - Amanda Silva de Sousa; Fabrizza Roberta Lemos Araújo; Giulliana Simões Castro Villela; David Normando (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate the effects of unilateral loss of the lower first permanent molar (L6) on the position and development of the lower third molar (L8). Material and Methods: Fifty-four panoramic radiographs of subjects with unilateral loss of L6 were examined. The L8 on the side of the L6 loss was compared with the L8 in the hemiarch without L6 loss (contralateral). The effect of L6 loss on the positioning of L8 was examined in all the samples (n=54), whereas the effect on the development of the third molar was examined in 38 patients with L8 with incomplete root formation. The Signs statistical test was used to evaluate the comparison between loss and contralateral hemiarches. Results: In 20 (37%) of 54 subjects, the L8 was better positioned in the hemiarch with loss of the lower first molar (p<0.001) compared with the control side. In the remaining 34 subjects, no difference was found. When only the L8 considered as impacted on the control side was examined (n=30), the cases with better positioning on the side with L6 loss increased to 66.6% (p<0.001). Conclusion: The loss of lower first molars improves the position of the lower third molar during its active eruption, mainly when the lower third molar is impacted. However, L6 loss does not affect the root development of lower third molars.